Method for preparing anhydrite by taking chemical gypsum as raw material and anhydrite prepared by method

By adding modifiers and water to chemical gypsum for pretreatment, and autoclaved heat treatment under specific temperature and steam pressure conditions, the high energy consumption and pollution problems of anhydrotest preparation in the prior art are solved, and efficient and environmentally friendly anhydrotest preparation is achieved, which improves the water resistance and strength of building materials.

CN119591334APending Publication Date: 2025-03-11WUHAN SANRUI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411699911.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, the process of preparing anhydrite from chemical gypsum consumes high energy and may lead to air pollution. The prepared building materials are insufficient in water resistance and strength, which limits the resource utilization of chemical gypsum.

Method used

A green and low-carbon preparation method is adopted, and aphrodisiacs are pretreated by adding harmless modifiers and water to chemical gypsum, adding seed crystal agents and accelerators, and then autoclaved heat treatment is carried out under conditions of ≥120°C and saturated steam pressure ≥0.2MPa to obtain aphrodisiacs with perfect crystallization and small particle size.

Benefits of technology

It has achieved low energy consumption and low carbon emission preparation of anhydroplaster. The product has high conversion rate, fine particle size and strong water resistance. It is suitable for the production of a variety of building materials and expands the application field of chemical gypsum.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591334A_ABST
    Figure CN119591334A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing anhydrite with chemical gypsum as a raw material and anhydrite prepared thereof.The preparation method comprises the steps that a harmless modifier and water are added into the chemical gypsum, a pretreatment material with the water content smaller than or equal to 40 wt% is obtained through pretreatment, a seed crystal agent and an accelerant are added into the pretreatment material and mixed to be uniform, and a precursor is obtained; and carrying out autoclaved heat treatment on the precursor at the temperature of more than or equal to 120 DEG C and the saturated vapor pressure of more than or equal to 0.2 MPa. Based on the method, a large amount of chemical gypsum can be consumed to prepare the anhydrite powder, the preparation process is low in carbon and low in cost, large-scale production is easy to achieve, and the prepared anhydrite is small in particle size (D50 is smaller than 10 micrometers), high in relative content of the anhydrite (high in anhydrite conversion rate) and low in soluble impurity content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gypsum production, in particular to a method for preparing anhydrite, and more particularly to a method for preparing anhydrite using chemical gypsum as a raw material and the anhydrite obtained by the preparation. Background Art

[0002] Chemical gypsum, also known as industrial by-product gypsum, refers to industrial solid waste generated in industrial production with calcium sulfate as the main component (CaSO4·2H2O as the main phase); among them, desulfurized gypsum and phosphogypsum are the most common, accounting for 85% of the total chemical gypsum. Others include titanium gypsum, citric acid gypsum and fluorinated gypsum (the main phase is type II anhydrite).

[0003] Specifically, phosphogypsum is a by-product of the wet production of phosphoric acid. Every ton of phosphoric acid produced (measured in P2O5) will produce 3-5 tons of phosphogypsum, which is widely distributed in the Yangtze River Basin. Desulfurization gypsum is a by-product formed when sulfur oxides are removed from coal-fired flue gas. It mainly comes from thermal power plants and is widely distributed in the northern region, forming a huge stockpile.

[0004] Specifically, calcium sulfate exists in the following phases: gypsum (CaSO4·2H2O), α-hemihydrate gypsum (α-CaSO4· 1 / 2H2O), β-hemihydrate gypsum (β-CaSO4· 1 / 2H2O), type III anhydrite (III-CaSO4), type II anhydrite (II-CaSO4) and type I anhydrite (I-CaSO4). Among them, type III anhydrite is unstable and absorbs moisture in the air to hydrate, becoming hemihydrated gypsum or gypsum; type I anhydrite is stable above 1250℃ and transforms into type II anhydrite when the temperature drops; type II anhydrite is referred to as anhydrite, which is stable in the air and difficult to hydrate in water.

[0005] At present, the main use of chemical gypsum is to produce building gypsum powder (mainly β-hemihydrate gypsum and containing a small amount of type III anhydrite) through calcination, and then produce various building materials, such as blocks, wall panels, mortar, etc.; on the one hand, its application field is not broad enough, and on the other hand, the building materials produced by it generally have defects such as low strength and poor water resistance, and can only be used in dry environments, which greatly limits the large-scale resource utilization of chemical gypsum.

[0006] As we all know, various building materials can be prepared using hard gypsum as raw material, and the water resistance of the prepared building materials is higher than that of building materials prepared mainly with hemihydrate gypsum, and the strength can be higher. It can even be used as outdoor and municipal building materials. Therefore, it can greatly expand the application field of chemical gypsum, which is conducive to more resource utilization of chemical gypsum and alleviate the threat of pollution.

[0007] In addition, the Mohs hardness of anhydrite is 3.0-3.5, and the specific gravity is 2.9-3.0g / cm 3 , three groups of complete cleavage; its physical properties are very similar to those of calcite, but it has high chemical stability and does not react with acids and alkalis. These properties determine that anhydrite powder can also replace heavy calcium carbonate as a polymer and paper filler, expanding the application field of chemical gypsum.

[0008] In the prior art, the process of preparing anhydrite from chemical gypsum (mainly CaSO4·2H2O) is calcined at ≥800℃; this process has high energy consumption. At the same time, if the raw materials are phosphogypsum, citric acid gypsum and titanium gypsum, phosphorus, fluorine, organic acid, heavy metals and other pollutants may diffuse into the atmosphere with the flue gas, causing real air pollution.

[0009] In view of this, in order to expand the application scope of chemical gypsum, the present invention proposes a green and low-carbon method for preparing anhydrite using chemical gypsum as raw material, and obtains anhydrite with perfect crystallization and fine particle size. Summary of the invention

[0010] The object of the present invention is to provide a green and low-carbon method for preparing anhydrite with perfect crystallization and fine particle size by using chemical gypsum as raw material.

[0011] The present invention adopts the following technical solution:

[0012] A method for preparing anhydrite using chemical gypsum as raw material, comprising:

[0013] Adding a harmless modifier and water to chemical gypsum, and obtaining a pretreated material with a moisture content of ≤40wt% after pretreatment;

[0014] Adding a seeding agent and a promoter to the pretreated material and mixing them well to obtain a precursor;

[0015] The precursor is subjected to autoclave heat treatment at ≥120°C and saturated vapor pressure ≥0.2MPa to obtain anhydrite.

[0016] Specifically, in the above technical scheme, the chemical gypsum refers to industrial waste slag with gypsum (CaSO4·2H2O) as the main phase component produced in the chemical production process; chemical gypsums such as phosphogypsum, citric acid gypsum and titanium gypsum contain a lot of residual acid, which not only pollutes the environment, but also is not conducive to the application of anhydrite as a building material. Therefore, when the chemical gypsum is highly acidic (pH<6), a harmless modifier needs to be added for pretreatment.

[0017] Specifically, in the above technical scheme, the seeding agent plays a role in inducing the crystallization of anhydrite, and can be the anhydrite powder obtained in the early stage; the addition of the accelerator realizes the conversion of CaSO4·2H2O to CaSO4 under specific temperature range (≥120°C) and specific saturated steam (≥0.11MPa) conditions. Since a certain amount of free water must exist in the precursor, it is speculated that its mechanism is still dissolution-recrystallization, and the accelerator catalyzes this process; in addition, in order to mix the seeding agent and the accelerator evenly, a small amount of water can be added first and then the seeding agent and the accelerator can be added into the pretreated material while stirring.

[0018] In the above technical solution, the seeding agent is a perfectly crystallized anhydrite powder, and its anhydrite content is ≥80wt%, and its particle size D50 is ≤5μm.

[0019] Preferably, in the above technical solution, the added amount of the seeding agent is 0.8-1.2wt% of the CaSO4·2H2O in the pretreated material.

[0020] In the above technical solution, the accelerator is at least one of water-soluble sodium dodecylbenzene sulfonate, stearate, polycarboxylate, ethylenediaminetetraacetic acid, maleic acid, succinic acid, tartaric acid, aluminum sulfate and magnesium sulfate.

[0021] Preferably, in the above technical solution, the added amount of the accelerator is 0.2-1.6wt% of the CaSO4·2H2O content in the pretreated material.

[0022] Furthermore, in the above technical solution, the harmless modifier is quicklime and / or carbide slag, and the amount added is to control the pH of the pretreated material to be 6-9.

[0023] Specifically, the harmless modifier is mainly used to solidify the residual acid in chemical gypsum, and at least one of quicklime and carbide slag can be selected; and its effective calcium oxide content should not be less than 60wt%.

[0024] Preferably, the pH of the pretreated material is used as a measure of the amount of harmless modifier added, and the pH of the pretreated material is controlled between 6-9; if the pH is less than 6, the impact of residual acid in chemical gypsum on the environment and product performance cannot be completely eliminated, and if the pH is greater than 9, the conversion rate of anhydrite will be affected.

[0025] Specifically, the moisture content of chemical gypsum is generally maintained at about 15-35wt%. After being fully stirred and mixed with the harmless modifier, its own moisture content is sufficient to complete the neutralization reaction of the residual acid. Therefore, generally no additional water is required; however, if the chemical gypsum is stored for a long time and its moisture content is reduced to below 10wt%, additional water needs to be added to ensure that the moisture content of the pretreated material is maintained at about 10-40wt%; in addition, the moisture content of the pretreated material should be controlled below 40wt%, because during the steaming process of the material, too high a moisture content will cause a decrease in heat transfer efficiency, which is not conducive to the conversion of anhydrite.

[0026] Preferably, in the above technical solution, if a harmless modifier is added to adjust the pH of the chemical gypsum, it is necessary to let it stand for a certain period of time to allow CaO to fully react with the residual acid in the chemical gypsum; standing means covering and storing the evenly mixed material for no less than 24 hours, preferably 72 hours or more, and the standing temperature is not lower than zero degrees; the purpose of covering is to prevent water evaporation.

[0027] Furthermore, in the above technical solution, the time of the autoclave heat treatment is 4-12 hours.

[0028] Preferably, in the above technical solution, the temperature and saturated steam pressure of the autoclave heat treatment are 120-230° C. and 0.11-2.8 MPa, respectively.

[0029] Specifically, in a preferred embodiment of the present invention, the method for preparing anhydrite using chemical gypsum as raw material comprises the following steps:

[0030] S1. Preprocessing

[0031] Adding a harmless modifier and water to chemical gypsum whose main phase component is CaSO4·2H2O, stirring evenly and / or standing to obtain a pretreated material with a pH of 6-9 and a water content of ≤40wt%;

[0032] S2. Mixing

[0033] Adding anhydrite powder as a seeding agent to the pretreated material in step S1, and adding an accelerator and stirring well to obtain a precursor with a moisture content of ≤40wt%;

[0034] Wherein, the promoter is preferably at least one of water-soluble sodium dodecylbenzene sulfonate, stearate, polycarboxylate, ethylenediaminetetraacetic acid, maleic acid, succinic acid, tartaric acid, aluminum sulfate and magnesium sulfate, and the addition amounts of the seeding agent and promoter are 0.2-1.8wt% and 0.2-1.6wt% of the CaSO4·2H2O content in the pretreated material, respectively;

[0035] S3, Autoclave Heat Treatment

[0036] The precursor in step S2 is placed in a steam-permeable but non-leaky container, placed in an autoclave, and heated until the temperature and saturated steam pressure in the autoclave are 120-230° C. and 0.11-2.8 MPa, respectively, and kept warm for 6-12 hours to obtain a semi-finished product;

[0037] S4. Post-processing

[0038] The semi-finished product in step S3 is dried and broken up to obtain anhydrite powder.

[0039] In step S4, the semi-finished product can be dried by any drying method, such as a rotary dryer, a three-pass dryer, a paddle dryer, a fluidized bed, etc.; the semi-finished product can also be broken up by various conventional methods, such as a cage mill, a powder mill, a claw crusher, a Raymond mill, etc.

[0040] In a specific embodiment of the present invention, the chemical gypsum is at least one of phosphogypsum, flue gas desulfurization gypsum, titanium gypsum and citric acid gypsum.

[0041] In a preferred embodiment of the present invention, during the heating process of the autoclave heat treatment, the heating rate is controlled to be 1-5°C / min.

[0042] In detail, in a specific embodiment of the present invention, the anhydrite powder prepared with various chemical gypsums as raw materials has a conversion rate R ≥ 95%, the anhydrite is perfectly crystallized and basically single crystal, the particles (also grains) are small, and the median diameter D50 of most particles (grains) is ≤ 15 μm.

[0043] The conversion rate R is defined as follows:

[0044]

[0045] In the formula,

[0046] R: conversion rate, %;

[0047] W T : The amount of CaSO4·2H2O converted into anhydrite in chemical gypsum;

[0048] W0: CaSO4·2H2O content in chemical gypsum, i.e., grade;

[0049] W R : CaSO4·2H2O content in anhydrite powder after full hydration.

[0050] The test method is as follows: first, take about 10g of anhydrite powder, add 15g of deionized water, stir, hydrate at room temperature for 24h, filter, and dry at 45℃; then test the crystal water content according to Article 10 of "GB / T 5484-2012 Chemical Analysis Method for Gypsum", and calculate the CaSO4·2H2O content W R .

[0051] For example, if the grade of a chemical gypsum is 86.5%, the CaSO4·2H2O content of the anhydrite powder product after full hydration is W R is 2.6%, and the anhydrite conversion rate R is 97.52%.

[0052] Another aspect of the present invention also provides anhydrite prepared by the above method.

[0053] Specifically, the anhydrite prepared above has a fine particle size, D50<10μm, a high relative content of anhydrite in the product, an anhydrite conversion rate ≥95%, water-soluble P2O5≤0.001wt%, and water-soluble F - ≤0.01wt%.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] (1) The preparation method provided by the present invention is energy-saving, low-carbon and low-cost. The traditional method for preparing anhydrite requires calcining chemical gypsum at a dry base of more than 800°C, and the theoretical energy consumption is more than 85kg standard coal / ton, while the energy consumed by the present invention is 12-18kg standard coal / ton, the energy saving effect is very significant, and there is basically no three wastes discharged during the production process;

[0056] (2) The preparation method provided by the present invention can achieve large-scale production. Only a few Φ2.68×38 horizontal autoclaves are needed to process 500,000 tons of chemical gypsum per year, while the maximum scale of the traditional calcination method is currently 350,000 tons / year;

[0057] (3) The anhydrite prepared by the present invention has a small particle size (D 50 <10μm), high relative content of anhydrite, high conversion rate of anhydrite, and low content of soluble impurities; used as a cementitious material, it has strong water resistance and high strength, and can also replace heavy calcium powder as a polymer filler, expanding the application of chemical gypsum, reducing the mining and consumption of calcium carbonate resources, and is beneficial to ecological environment protection;

[0058] (4) For phosphogypsum, the present invention completes harmless treatment and resource utilization at one time, and can directly use phosphogypsum discharged from phosphoric acid production as raw material, thereby reducing costs and not generating secondary pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1This is a process flow chart of preparing anhydrite using chemical gypsum (specifically phosphogypsum) as raw material according to Example 1 of the present invention;

[0060] Figure 2 Figure 2 is a test result diagram of the phosphogypsum raw material and the prepared anhydrite of Example 1 of the present invention (2a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite, 2b is the particle size distribution test result of the prepared anhydrite powder, and 2c is the SEM photo of the prepared anhydrite powder);

[0061] Figure 3 Figure 3 is a test result diagram of the phosphogypsum raw material and the prepared anhydrite of Example 2 of the present invention (3a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite, 3b is the particle size distribution test result of the prepared anhydrite powder, and 3c is the SEM photo of the prepared anhydrite powder);

[0062] Figure 4 Figure 4 is a test result diagram of the phosphogypsum raw material and the prepared anhydrite of Example 3 of the present invention (4a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite, 4b is the particle size distribution test result of the prepared anhydrite powder, and 4c is the SEM photo of the prepared anhydrite powder);

[0063] Figure 5 Figure 5 is a test result diagram of the phosphogypsum raw material and the prepared anhydrite of Example 4 of the present invention (5a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite, 5b is the particle size distribution test result of the prepared anhydrite powder, and 5c is the SEM photo of the prepared anhydrite powder);

[0064] Figure 6 Figure 6 is a test result diagram of the phosphogypsum raw material and the prepared anhydrite of Example 5 of the present invention (6a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite, 6b is the particle size distribution test result of the prepared anhydrite powder, and 6c is the SEM photo of the prepared anhydrite powder);

[0065] Figure 7 Figure 7 is a test result diagram of the phosphogypsum raw material and the prepared anhydrite of Example 6 of the present invention (7a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite, 7b is the particle size distribution test result of the prepared anhydrite powder, and 7c is the SEM photo of the prepared anhydrite powder);

[0066] Figure 8Figure 8 is a test result diagram of the phosphogypsum raw material and the prepared anhydrite of Example 7 of the present invention (8a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite, 8b is the particle size distribution test result of the prepared anhydrite powder, and 8c is the SEM photo of the prepared anhydrite powder);

[0067] Fig. 9 Figure 9 is a test result diagram of the phosphogypsum raw material and the prepared anhydrite of Example 8 of the present invention (9a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite, 9b is the particle size distribution test result of the prepared anhydrite powder, and 9c is the SEM photo of the prepared anhydrite powder);

[0068] Fig.10 10a is an XRD spectrum of the phosphogypsum raw material and the prepared anhydrite of Example 9 of the present invention, 10b is a particle size distribution test result of the prepared anhydrite powder, and 10c is a SEM photo of the prepared anhydrite powder;

[0069] Fig.11 11a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite, 11b is the particle size distribution test result of the prepared anhydrite powder, and 11c is the SEM photo of the prepared anhydrite powder. DETAILED DESCRIPTION

[0070] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.

[0071] All the following embodiments are only used to illustrate the present invention, but are not limited to the scope of the present invention.

[0072] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the protection scope of the present invention.

[0073] Example 1

[0074] The embodiment of the present invention provides a method for preparing anhydrite using phosphogypsum (CaSO4·2H2O content of 87.2wt%, water content of 22.54wt%, pH of 3.6) as raw material, such as Figure 1 As shown, the specific steps include:

[0075] S1. Preprocessing

[0076] Take 100 kg of phosphogypsum, put it in a mixing barrel, add 216.9 g (0.28% of dry phosphogypsum) quicklime (effective CaO is 66.4%), stir while adding, and let it stand for 24 hours to react, to obtain a pretreated material with a pH of 7.5;

[0077] S2. Mixing

[0078] Add 337.7 g (0.5% of the CaSO4·2H2O content in the phosphogypsum) of commercially available anhydrite powder as a seeding agent to the pretreated material in step S1, and add 202.6 g (0.3% of the CaSO4·2H2O content in the phosphogypsum) of polycarboxylate as a promoter, stir evenly, and obtain a precursor;

[0079] S3, Autoclave Heat Treatment

[0080] The precursor in step S2 is placed in a steam-permeable but non-leaking autoclave container, placed in an autoclave, and heated at a heating rate of 3°C / min until the temperature and saturated steam pressure in the autoclave are 195°C and 1.4MPa, respectively, and then kept at this temperature and pressure for 6.5h to obtain a semi-finished product;

[0081] S4. Post-processing

[0082] The semi-finished product obtained in step S3 is placed in a rotary dryer for drying, and is broken up by a Raymond grinder to obtain anhydrite powder.

[0083] Figure 2 a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite in Example 1 of the present invention; it can be seen from the figure that the CaSO4·2H2O in the raw material phosphogypsum has been converted into CaSO4.

[0084] Figure 2 b is the particle size distribution test result of the anhydrite powder prepared in Example 1 of the present invention; it can be seen from the figure that the anhydrite powder D 50 =3.97μm, D 90 =9.53μm.

[0085] Figure 2 c is a SEM photograph of the anhydrite powder prepared in Example 1 of the present invention; it can be seen from the figure that the anhydrite powder has a relatively uniform and compact crystal structure, which appears as stacked rectangular parallelepipeds.

[0086] Example 2

[0087] The embodiment of the present invention provides a method for preparing anhydrite using phosphogypsum (CaSO4·2H2O content of 83.0wt%, water content of 18.68wt%, pH of 2.4) as raw material, such as Figure 1 As shown, the specific steps include:

[0088] S1. Preprocessing

[0089] Take 100 kg of phosphogypsum, put it in a mixing barrel, add 796.9 g (0.98% of dry phosphogypsum) quicklime (effective CaO is 66.4%), stir while adding, and let it stand for 72 hours to react, to obtain a pretreated material with a pH of 8.2;

[0090] S2. Mixing

[0091] Add 135 g (0.2% of the CaSO4·2H2O content in the phosphogypsum) of the anhydrite powder prepared in Example 1 as a seeding agent to the pretreated material in step S1, and add 67.5 g (0.1% of the CaSO4·2H2O content in the phosphogypsum) of sodium dodecyl sulfate as a promoter, stir evenly, and obtain a precursor;

[0092] S3, Autoclave Heat Treatment

[0093] The precursor in step S2 is placed in a steam-permeable but non-leaking autoclave container, placed in an autoclave, and heated at a heating rate of 3°C / min until the temperature and saturated steam pressure in the autoclave are 215°C and 2.1MPa, respectively, and then kept at this temperature and pressure for 12 hours to obtain a semi-finished product;

[0094] S4. Post-processing

[0095] The semi-finished product obtained in step S3 is placed in a rotary dryer for drying, and is broken up by a claw type crusher to obtain anhydrite powder.

[0096] Figure 3 a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite in Example 2 of the present invention; it can be seen from the figure that the CaSO4·2H2O in the raw material phosphogypsum has been converted into CaSO4.

[0097] Figure 3 b is the particle size distribution test result of the anhydrite powder prepared in Example 2 of the present invention; it can be seen from the figure that the anhydrite powder D 50 =3.32μm, D 90 =7.65μm.

[0098] Figure 3 c is a SEM photograph of the anhydrite powder prepared in Example 2 of the present invention; it can be seen from the figure that the anhydrite powder has a relatively uniform and compact crystal structure, which appears as stacked cubes.

[0099] Example 3

[0100] The embodiment of the present invention provides a method for preparing anhydrite using phosphogypsum (CaSO4·2H2O content of 88.9wt%, water content of 3.56wt%, pH of 3.2) as raw material, such as Figure 1 As shown, the specific steps include:

[0101] S1. Preprocessing

[0102] Take 100 kg of phosphogypsum, put it in a mixing barrel, add 964.4 g (1% of dry phosphogypsum) of carbide slag (effective CaO is 62.1%), and add 13.8 kg of water at the same time, stir while adding, and let it stand for 48 hours to react, and obtain a pretreated material with a pH of 8.5;

[0103] S2. Mixing

[0104] Add 514 g (0.6% of the CaSO4·2H2O content in the phosphogypsum) of the anhydrite powder prepared in Example 1 as a seeding agent to the pretreated material in step S1, and add 257.2 g (0.3% of the CaSO4·2H2O content in the phosphogypsum) of ethylenediaminetetraacetic acid as a promoter, stir evenly, and obtain a precursor;

[0105] S3, Autoclave Heat Treatment

[0106] The precursor in step S2 is placed in a steam-permeable but non-leaky autoclave container, placed in an autoclave, and heated at a heating rate of 2°C / min until the temperature and saturated steam pressure in the autoclave are 200°C and 1.55MPa, respectively, and then kept at this temperature and pressure for 9 hours to obtain a semi-finished product;

[0107] S4. Post-processing

[0108] The semi-finished product obtained in step S3 is placed in a rotary dryer for drying, and is broken up by a Raymond grinder to obtain anhydrite powder.

[0109] Figure 4 a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite in Example 3 of the present invention; it can be seen from the figure that the CaSO4·2H2O in the raw material phosphogypsum has been converted into CaSO4.

[0110] Figure 4 b is the particle size distribution test result of the anhydrite powder prepared in Example 3 of the present invention; it can be seen from the figure that the anhydrite powder D 50 =7.04μm, D 90 =20.2μm.

[0111] Figure 4c is a SEM photograph of the anhydrite powder prepared in Example 3 of the present invention; it can be seen from the figure that the anhydrite powder has a relatively uniform and compact crystal structure, which appears as stacked rectangular parallelepipeds.

[0112] Example 4

[0113] The embodiment of the present invention provides a method for preparing anhydrite using phosphogypsum (CaSO4·2H2O content of 89.5wt%, water content of 12.77wt%, pH of 5.1) as raw material, such as Figure 1 As shown, the specific steps include:

[0114] S1. Preprocessing

[0115] Take 100 kg of phosphogypsum, put it in a mixing barrel, add 61.1 g (0.07% of dry phosphogypsum) quicklime (effective CaO is 66.4%), stir while adding, and let it stand for 24 hours to react, to obtain a pretreated material with a pH of 7.3;

[0116] S2. Mixing

[0117] Add 780.7 g (1.0% of the CaSO4·2H2O content in the phosphogypsum) of the anhydrite powder prepared in Example 1 as a seeding agent to the pretreated material in step S1, and add 4684.3 g (6% of the CaSO4·2H2O content in the phosphogypsum) of maleic acid as a promoter, stir evenly, and obtain a precursor;

[0118] S3, Autoclave Heat Treatment

[0119] The precursor in step S2 is placed in a steam-permeable but non-leaking autoclave container, placed in an autoclave, and heated at a heating rate of 5°C / min until the temperature and saturated steam pressure in the autoclave are 120°C and 0.11 MPa, respectively, and then kept at this temperature and pressure for 12 hours to obtain a semi-finished product;

[0120] S4. Post-processing

[0121] The semi-finished product obtained in step S3 is placed in a rotary dryer for drying, and is broken up by a claw type crusher to obtain anhydrite powder.

[0122] Figure 5 a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite in Example 4 of the present invention; it can be seen from the figure that the CaSO4·2H2O in the raw material phosphogypsum has been converted into CaSO4.

[0123] Figure 5 b is the particle size distribution test result of the anhydrite powder prepared in Example 4 of the present invention; it can be seen from the figure that the anhydrite powder D 50 =5.72μm, D90 =17.3μm.

[0124] Figure 5 c is a SEM photograph of the anhydrite powder prepared in Example 4 of the present invention; it can be seen from the figure that the anhydrite powder has a relatively uniform and compact crystal structure, which appears as stacked cubes.

[0125] Example 5

[0126] The embodiment of the present invention provides a method for preparing anhydrite using phosphogypsum (CaSO4·2H2O content of 95.9wt%, water content of 4.87wt%, pH of 4.5) as raw material, such as Figure 1 As shown, the specific steps include:

[0127] S1. Preprocessing

[0128] Take 100 kg of phosphogypsum, put it in a mixing barrel, add 104.6 g (0.11% of dry phosphogypsum) quicklime (effective CaO is 66.4%), and add 13.2 kg of water at the same time, stir while adding, and after standing for 24 hours, a pretreated material with a pH of 6.8 is obtained;

[0129] S2. Mixing

[0130] Add 1642.1 g (1.8% of the CaSO4·2H2O content in the phosphogypsum) of the anhydrite powder prepared in Example 1 as a seeding agent to the pretreated material in step S1, and add 5473.8 g (6% of the CaSO4·2H2O content in the phosphogypsum) of magnesium sulfate as a promoter, stir evenly, and obtain a precursor;

[0131] S3, Autoclave Heat Treatment

[0132] The precursor in step S2 is placed in a steam-permeable but non-leaking autoclave container, placed in an autoclave, and heated at a heating rate of 4°C / min until the temperature and saturated steam pressure in the autoclave are 140°C and 0.2MPa, respectively, and then kept at this temperature and pressure for 10.5h to obtain a semi-finished product;

[0133] S4. Post-processing

[0134] The semi-finished product obtained in step S3 is placed in a rotary dryer for drying, and is broken up by a Raymond grinder to obtain anhydrite powder.

[0135] Figure 6 a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite in Example 5 of the present invention; it can be seen from the figure that the CaSO4·2H2O in the raw material phosphogypsum has been converted into CaSO4.

[0136] Figure 6b is the particle size distribution test result of the anhydrite powder prepared in Example 5 of the present invention; it can be seen from the figure that the anhydrite powder D 50 =4.87μm, D 90 =11.5μm.

[0137] Figure 6 c is a SEM photograph of the anhydrite powder prepared in Example 5 of the present invention; it can be seen from the figure that the anhydrite powder has a relatively uniform and compact crystal structure, which appears as stacked cubes.

[0138] Example 6

[0139] The embodiment of the present invention provides a method for preparing anhydrite using phosphogypsum (CaSO4·2H2O content of 89.9wt%, water content of 7.54wt%, pH of 5.6) as raw material, such as Figure 1 As shown, the specific steps include:

[0140] S1. Preprocessing

[0141] Take 100 kg of phosphogypsum, put it in a mixing barrel, add 37.0 g (0.04% of dry phosphogypsum) of carbide slag (effective CaO is 62.1%), and add 9.52 kg of water at the same time, stir while adding, and let it stand for reaction for 24 hours to obtain a pretreated material with a pH of 7.2;

[0142] S2. Mixing

[0143] Add 1246.8 g (1.5% of the CaSO4·2H2O content in the phosphogypsum) of the anhydrite powder prepared in Example 1 as a seeding agent to the pretreated material in step S1, and add 2909.3 g (3.5% of the CaSO4·2H2O content in the phosphogypsum) of aluminum sulfate as a promoter, stir evenly, and obtain a precursor;

[0144] S3, Autoclave Heat Treatment

[0145] The precursor in step S2 is placed in a steam-permeable but non-leaking autoclave container, placed in an autoclave, and heated at a heating rate of 4°C / min until the temperature and saturated steam pressure in the autoclave are 155°C and 0.54MPa, respectively, and then kept at this temperature and pressure for 10.5h to obtain a semi-finished product;

[0146] S4. Post-processing

[0147] The semi-finished product obtained in step S3 is placed in a rotary dryer for drying, and is broken up by a Raymond grinder to obtain anhydrite powder.

[0148] Figure 5a is the XRD spectrum of the phosphogypsum raw material and the prepared anhydrite in Example 6 of the present invention; it can be seen from the figure that the CaSO4·2H2O in the raw phosphogypsum has been converted into CaSO4.

[0149] Figure 5 b is the particle size distribution test result of the anhydrite powder prepared in Example 6 of the present invention; it can be seen from the figure that the anhydrite powder D 50 =6.15μm, D 90 =16.2μm.

[0150] Figure 5 c is a SEM photograph of the anhydrite powder prepared in Example 6 of the present invention; it can be seen from the figure that the anhydrite powder has a relatively uniform and compact crystal structure, which appears as stacked cubes.

[0151] Example 7

[0152] The embodiment of the present invention provides a method for preparing anhydrite using desulfurized gypsum (CaSO4·2H2O content is 94.6wt%, water content is 9.6wt%) as raw material, such as Figure 1 As shown, the specific steps include:

[0153] S1. Mixing

[0154] Take 100 kg of desulfurized gypsum, put it in a stirring barrel, add 1282.8 g (1.5% of the CaSO4·2H2O content in the desulfurized gypsum) of commercially available anhydrite powder as a seeding agent, add 2993.1 g (3.5% of the CaSO4·2H2O content in the desulfurized gypsum) of maleic acid as a promoter, and add 7.11 kg of water, stir evenly, and obtain a precursor;

[0155] S2. Autoclave heat treatment

[0156] The precursor in step S1 is placed in a steam-permeable but non-leaking autoclave container, placed in an autoclave, and heated at a heating rate of 5°C / min until the temperature and saturated steam pressure in the autoclave are 230°C and 2.8MPa, respectively, and then kept at this temperature and pressure for 8h to obtain a semi-finished product;

[0157] S3, post-processing

[0158] The semi-finished product obtained in step S2 is placed in a rotary dryer for drying, and is broken up by a claw type crusher to obtain anhydrite powder.

[0159] Figure 6 a is the XRD spectrum of the desulfurized gypsum raw material and the prepared anhydrite in Example 7 of the present invention; it can be seen from the figure that the CaSO4·2H2O in the raw material desulfurized gypsum has been converted into CaSO4.

[0160] Figure 6 b is the particle size distribution test result of the anhydrite powder prepared in Example 7 of the present invention; it can be seen from the figure that the anhydrite powder D 50 =8.17μm, D 90 =54.8μm.

[0161] Figure 6 c is a SEM photograph of the anhydrite powder prepared in Example 7 of the present invention; it can be seen from the figure that the anhydrite powder has a relatively uniform and compact crystal structure, which appears as stacked cubes.

[0162] Example 8

[0163] The embodiment of the present invention provides a method for preparing anhydrite using desulfurized gypsum (CaSO4·2H2O content is 85wt%, water content is 7.7wt%) as raw material, such as Figure 1 As shown, the specific steps include:

[0164] S1. Mixing

[0165] Take 100 kg of desulfurized gypsum, put it in a stirring barrel, add 1176.8 g (1.5% of the CaSO4·2H2O content in the desulfurized gypsum) of commercially available anhydrite powder as a seeding agent, add 3138.2 g (4% of the CaSO4·2H2O content in the desulfurized gypsum) of succinic acid as a promoter, and add 9.35 kg of water, stir evenly, and obtain a precursor;

[0166] S2. Autoclave heat treatment

[0167] The precursor in step S1 is placed in a steam-permeable but non-leaking autoclave container, placed in an autoclave, and heated at a heating rate of 3°C / min until the temperature and saturated steam pressure in the autoclave are 225°C and 2.55MPa, respectively, and then kept at this temperature and pressure for 9 hours to obtain a semi-finished product;

[0168] S3, post-processing

[0169] The semi-finished product obtained in step S2 is placed in a rotary dryer for drying, and is broken up by a claw type crusher to obtain anhydrite powder.

[0170] Figure 7 a is the XRD spectrum of the desulfurized gypsum raw material and the prepared anhydrite in Example 8 of the present invention; it can be seen from the figure that the CaSO4·2H2O in the raw material desulfurized gypsum has been converted into CaSO4.

[0171] Figure 7 b is the particle size distribution test result of the anhydrite powder prepared in Example 8 of the present invention; it can be seen from the figure that the anhydrite powder D 50=7.31μm, D 90 =22.6μm.

[0172] Figure 7 c is a SEM photograph of the anhydrite powder prepared in Example 8 of the present invention; it can be seen from the figure that the anhydrite powder has a relatively uniform and compact crystal structure, which appears as stacked cubes.

[0173] Example 9

[0174] The embodiment of the present invention provides a method for preparing anhydrite using citric acid gypsum (CaSO4·2H2O content of 87.0wt%, water content of 15.8wt%, pH of 4.2) as raw material, such as Figure 1 As shown, the specific steps include:

[0175] S1. Preprocessing

[0176] Take 100 kg of citric acid gypsum, put it in a mixing barrel, add 193.7 g (0.23% of dry citric acid gypsum) quicklime (effective CaO is 66.4%), stir while adding, and let it stand for 72 hours to react, and obtain a pretreated material with a pH of 7.2;

[0177] S2. Mixing

[0178] Add 732.5 g (1% of the CaSO4·2H2O content in the citric acid gypsum) of commercially available anhydrite powder as a seeding agent to the pretreated material in step S1, and add 586 g (0.8% of the CaSO4·2H2O content in the citric acid gypsum) of stearate as a promoter, stir evenly, and obtain a precursor;

[0179] S3, Autoclave Heat Treatment

[0180] The precursor in step S2 is placed in a steam-permeable but non-leaking autoclave container, placed in an autoclave, and heated at a heating rate of 3°C / min until the temperature and saturated steam pressure in the autoclave are 135°C and 0.31MPa, respectively, and then kept at this temperature and pressure for 10 hours to obtain a semi-finished product;

[0181] S4. Post-processing

[0182] The semi-finished product obtained in step S3 is placed in a rotary dryer for drying, and is broken up by a claw type crusher to obtain anhydrite powder.

[0183] Figure 8 a is the XRD spectrum of the citric acid gypsum raw material and the prepared anhydrite in Example 9 of the present invention; it can be seen from the figure that the CaSO4·2H2O in the raw material citric acid gypsum has been converted into CaSO4.

[0184] Figure 8 b is the particle size distribution test result of the anhydrite powder prepared in Example 9 of the present invention; it can be seen from the figure that the anhydrite powder D 50 =3.89μm, D 90 =9.43μm.

[0185] Figure 8 c is a SEM photograph of the anhydrite powder prepared in Example 9 of the present invention; it can be seen from the figure that the anhydrite powder has a relatively uniform and compact crystal structure, which appears as stacked cubes.

[0186] Example 10

[0187] The embodiment of the present invention provides a method for preparing anhydrite using titanium gypsum (CaSO4·2H2O content is 80.2wt%, water content is 12.6wt%) as raw material, such as Figure 1 As shown, the specific steps include:

[0188] S1. Preprocessing

[0189] Take 100 kg of titanium gypsum, put it in a stirring barrel, add 96.1 g (0.11% of dry titanium gypsum) quicklime (effective CaO is 66.4%), stir while adding, and let it stand for 24 hours to react, to obtain a pretreated material with a pH of 7.2;

[0190] S2. Mixing

[0191] Add 700.9 g (1% of the CaSO4·2H2O content in the titanium gypsum) of commercially available anhydrite powder as a seeding agent to the pretreated material in step S1, and add 3154.3 g (4.5% of the CaSO4·2H2O content in the titanium gypsum) of tartaric acid as a promoter, stir evenly, and obtain a precursor;

[0192] S3, Autoclave Heat Treatment

[0193] The precursor in step S2 is placed in a steam-permeable but non-leaking autoclave container, placed in an autoclave, and heated at a heating rate of 2°C / min until the temperature and saturated steam pressure in the autoclave are 215°C and 2.1MPa, respectively, and then kept at this temperature and pressure for 9 hours to obtain a semi-finished product;

[0194] S4. Post-processing

[0195] The semi-finished product obtained in step S3 is placed in a rotary dryer for drying, and is broken up by a Raymond grinder to obtain anhydrite powder.

[0196] Fig.11a is the XRD spectrum of the titanium gypsum raw material and the prepared anhydrite in Example 10 of the present invention; it can be seen from the figure that the CaSO4·2H2O in the raw titanium gypsum has been converted into CaSO4.

[0197] Fig.11 b is the particle size distribution test result of the anhydrite powder prepared in Example 10 of the present invention; it can be seen from the figure that the anhydrite powder D 50 =9.03μm, D 90 =20.9μm.

[0198] Fig.11 c is a SEM photograph of the anhydrite powder prepared in Example 10 of the present invention; it can be seen from the figure that the anhydrite powder has a relatively uniform and compact crystal structure, which appears as stacked cubes.

[0199] The conversion rate R of the anhydrite prepared in Test Examples 1-10 was determined.

[0200] The test method is:

[0201] First, take about 10g of the product anhydrite powder, add 15g of deionized water, stir and hydrate at room temperature for 24h, filter and dry at 45℃; then test the crystal water content according to Article 10 of "GB / T 5484-2012 Chemical Analysis Method for Gypsum" and calculate the CaSO4·2H2O content W R .

[0202] For example, the grade W0 of a chemical gypsum is 86.5%, and the CaSO4·2H2O content of the anhydrite powder product after full hydration is W R is 2.6%, and the anhydrite conversion rate R is 97.0%.

[0203] The conversion rate R is defined as follows

[0204]

[0205] In the formula,

[0206] R: conversion rate, %;

[0207] W T : The amount of CaSO4·2H2O converted into anhydrite in chemical gypsum;

[0208] W0: CaSO4·2H2O content in chemical gypsum, i.e., grade;

[0209] W R : CaSO4·2H2O content in anhydrite powder after full hydration.

[0210] In addition, the particle size distribution, whiteness, free acid content (ICP-AES method, detection limit of 0.001wt%) of the hard gypsum prepared in test examples 1-10, and the free acid content in the condensed water discharged during the autoclaving process (ICP-AES method, detection limit of 0.001wt%) are shown in Table 1 below.

[0211] Table 1 Conversion rate and particle size distribution of anhydrite prepared in Examples 1-10 50 , whiteness test results

[0212]

[0213]

[0214] As can be seen from Table 1, different chemical gypsums can be prepared by the preparation method of the present invention to produce anhydrite powder with an anhydrite conversion rate of ≥ 95%, the pH of the powder is between 6 and 9, and the particle size distribution of the anhydrite crystal is D 50 <10μm, and its whiteness varies according to the different chemical gypsum raw materials used; the residual free acid content in the prepared anhydrite powder meets the emission standard of Class I general industrial solid waste in the "GB 18599-2020 General Industrial Solid Waste Storage and Landfill Pollution Control Standard", which proves that the anhydrite preparation process of the present invention not only realizes the resource utilization of chemical gypsum, but also completes the harmless treatment of chemical gypsum; in addition, the production process of anhydrite basically has no three wastes discharged, and the free acid content in the condensed water discharged during the steaming process meets the emission requirements in the "GB 8978-1996 Comprehensive Sewage Discharge Standard", and the condensed water can be used as the water needed to be added in the mixing process, and returned to the anhydrite preparation process system to realize the recycling of wastewater.

[0215] Finally, the method of the present invention is only a preferred embodiment and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing anhydrite using chemical gypsum as raw material, characterized in that: include: Adding a harmless modifier and water to chemical gypsum, and obtaining a pretreated material with a moisture content of ≤40wt% after pretreatment; Adding a seeding agent and a promoter to the pretreated material and mixing them well to obtain a precursor; The precursor is subjected to autoclave heat treatment at ≥120°C and saturated vapor pressure ≥0.11MPa to obtain anhydrite.

2. The method for preparing anhydrite using chemical gypsum as raw material according to claim 1, characterized in that: The seeding agent is anhydrite powder with perfect crystallization, and its anhydrite content is ≥80wt%, and its particle size D50 is ≤5μm; Preferably, the amount of the seeding agent added is 0.2-1.8wt% of the CaSO4·2H2O content in the pretreated material.

3. The method for preparing anhydrite using chemical gypsum as raw material according to claim 1, characterized in that: The accelerator is at least one of water-soluble sodium dodecylbenzene sulfonate, stearate, polycarboxylate, ethylenediaminetetraacetic acid, maleic acid, succinic acid, tartaric acid, aluminum sulfate and magnesium sulfate; Preferably, the amount of the accelerator added is 0.2-1.6 wt % of the CaSO4·2H2O content in the pretreated material.

4. The method for preparing anhydrite using chemical gypsum as raw material according to any one of claims 1 to 3, characterized in that: The harmless modifier is quicklime and / or carbide slag, and the amount of the added agent is to control the pH of the pretreated material to be 6-9.

5. The method for preparing anhydrite using chemical gypsum as raw material according to any one of claims 1 to 4, characterized in that: The time of the autoclave heat treatment is 6-12h; Preferably, the temperature and saturated steam pressure of the autoclave heat treatment are 120-230° C. and 0.11-2.8 MPa, respectively.

6. The method for preparing anhydrite using chemical gypsum as raw material according to any one of claims 1 to 5, characterized in that: The specific steps include: S1. Preprocessing Adding a harmless modifier and water to chemical gypsum whose main phase component is CaSO4·2H2O, stirring evenly and / or standing to obtain a pretreated material with a pH of 6-9 and a water content of ≤40wt%; S2. Mixing Adding anhydrite powder as a seeding agent to the pretreated material in step S1, and adding an accelerator and stirring well to obtain a precursor with a moisture content of ≤40wt%; Wherein, the promoter is preferably at least one of water-soluble sodium dodecylbenzene sulfonate, stearate, polycarboxylate, ethylenediaminetetraacetic acid, maleic acid, succinic acid, tartaric acid, aluminum sulfate and magnesium sulfate, and the addition amounts of the seeding agent and promoter are 0.2-1.8wt% and 0.2-1.6wt% of the CaSO4·2H2O content in the pretreated material, respectively; S3, Autoclave Heat Treatment The precursor in step S2 is placed in a steam-permeable but non-leaky container, placed in an autoclave, and heated until the temperature and saturated steam pressure in the autoclave are 120-230° C. and 0.11-2.8 MPa, respectively, and kept warm for 6-12 hours to obtain a semi-finished product; S4. Post-processing The semi-finished product in step S3 is dried and broken up to obtain anhydrite powder.

7. The method for preparing anhydrite using chemical gypsum as raw material according to any one of claims 1 to 6, characterized in that: The chemical gypsum is at least one of phosphogypsum, flue gas desulfurization gypsum, titanium gypsum and citric acid gypsum.

8. The method for preparing anhydrite using chemical gypsum as raw material according to any one of claims 1 to 7, characterized in that: During the heating process of the autoclave heat treatment, the heating rate is controlled to be 1-5°C / min.

9. Anhydrite prepared by the method according to any one of claims 1 to 8.

10. Anhydrite according to claim 9, characterized in that The particle size is fine, D50<10μm, the relative content of anhydrite in the product is high, the anhydrite conversion rate is ≥95%, the water-soluble P2O5≤0.0015wt%, the water-soluble F - ≤0.01wt%.